2020
DOI: 10.3390/molecules25153544
|View full text |Cite
|
Sign up to set email alerts
|

The Bioaccessibility of Antioxidants in Black Currant Puree after High Hydrostatic Pressure Treatment

Abstract: The aim of the study was to investigate the effect of high-pressure processing (HPP) and thermal processing (TP) on the bioaccessibility of vitamin C and anthocyanins as well as changes in the antioxidant capacity (AC) using ABTS+• and DPPH• tests on blackcurrant (Ribes nigrum L.) puree during the steps in the digestive process. The puree was subjected to HPP at 200, 400, and 600 MPa for 5 min (room temperature) or TP at 85 °C for 10 min. The controls were untreated puree (P) and fruit crushed in a mortar (M).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…We reported that the BAc of vitamin C in dialysate was unfortunately very low and reached only 1% in samples treated using HHP in 400 and 600 MPa. Due to the possibility of the absorption of vitamin C just after gastric digestion, BAc after that stage was considered and ranged between 60% in pasteurized samples and 90% in HHP 400 and 600 MPa [24]. The differences in the bioaccessibility obtained in our studies could largely be due to using a different food matrix, which was also noted by other researchers.…”
Section: Stability and Bioaccessibility Of Vitamin C After Sccd Treatmentmentioning
confidence: 48%
See 3 more Smart Citations
“…We reported that the BAc of vitamin C in dialysate was unfortunately very low and reached only 1% in samples treated using HHP in 400 and 600 MPa. Due to the possibility of the absorption of vitamin C just after gastric digestion, BAc after that stage was considered and ranged between 60% in pasteurized samples and 90% in HHP 400 and 600 MPa [24]. The differences in the bioaccessibility obtained in our studies could largely be due to using a different food matrix, which was also noted by other researchers.…”
Section: Stability and Bioaccessibility Of Vitamin C After Sccd Treatmentmentioning
confidence: 48%
“…Other authors indicated the total anthocyanin content in blackcurrants to be between 160-411 mg/100 g of fresh fruit [30,31]. In our previous study, the total anthocyanin content in blackcurrant was determined as 737 mg/kg of raw material [24]. The lower anthocyanin content in the raw material compared to juice may be related to the higher concentration of pectin in the fruits, which are able to bind anthocyanins in plant tissue.…”
Section: Stability and Bioaccessibility Of Anthocyanins And Determination Of Delphinidin Metabolites After In Vitro Gastro-intestinal Digmentioning
confidence: 73%
See 2 more Smart Citations
“…Over the past 30 years, the interest of scientists in the use of HHP in various scientific fields has been systematically increasing (Elamin et al, 2015;Kadam et al, 2012;Mota et al, 2013). HHP allows for extending the shelf life of food by reducing the number of microorganisms or reducing the activity of enzymes (Huang et al, 2013;Kultur et al, 2017;Mota et al, 2013) while maintaining the properties, for example, color, taste, and nutrients (Andres et al, 2016;Huang et al, 2013;Janowicz & Lenart, 2015;Jayachandran et al, 2015;Kouniaki et al, 2004;Mastello et al, 2018;Tribst et al, 2016;Trych et al, 2020). The HHP belongs to unconventional methods of food preservation and it is an alternative or an addition to conventional treatments, mainly thermal.…”
Section: 3mentioning
confidence: 99%